2005
DOI: 10.1016/j.ijgo.2004.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Mode of delivery and pelvic floor muscle strength and sexual function after childbirth

Abstract: Pelvic floor muscle strength and mode of delivery did not affect sexual function in our study participants. The muscular component of female sexual function should be further investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
54
1
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 19 publications
7
54
1
14
Order By: Relevance
“…Other studies investigating dyspareunia in pregnant and postpartum women found no relationship between weak PFM and dyspareunia [24,25]. Both studies had fewer women in their analysis compared to our study, 68 and 110 respectively.…”
Section: Discussioncontrasting
confidence: 73%
“…Other studies investigating dyspareunia in pregnant and postpartum women found no relationship between weak PFM and dyspareunia [24,25]. Both studies had fewer women in their analysis compared to our study, 68 and 110 respectively.…”
Section: Discussioncontrasting
confidence: 73%
“…Ancak, sezaryen doğum ve cinsel işlev bozukluğu arasında bildirilen ilişki tutarsızdır (25) . Vajinal yolla ve sezaryen ile doğum yapan kadınlar arasında doğum yönte-minin cinsel işleve etkisi tespit edilmemiştir (26) . Hannah ve ark.…”
Section: Discussionunclassified
“…Dahası, doğum yönteminin postpartum cinsel işlevleri nasıl etkilediğine yönelik az sayıda çalışma mevcuttur (10) . Biz, Türk kadınları arasında postpartum cinsel işlevleri araştıran yalnızca bir çalışmaya rastladık (11) . Bu çalışmamızda, halen gelişmekte olan bir ülke olan Türkiye'de, kadın popülasyonunda doğum yöntemi-nin postpartum dönemde cinsel fonksiyonu etkileyip etkilemediğini araştırmayı amaçlamadık.…”
Section: Introductionunclassified
“…Meanwhile, Baytur et al 9 did not find a correlation between PFM strength (using the perineometer) and sexual function (through the FSFI questionnaire) postpartum. However, a PFM training program with nonpregnant women found that those with weak PFMs and who received training had positive results in sexual function, also verified through the FSFI 35 .…”
Section: Pfm Strength and Sexual Functionmentioning
confidence: 97%
“…The pelvic floor is the only transverse muscle group of the human body that supports load, and it is responsible for several functions such as: support of the abdominal and pelvic organs [5][6][7] , maintenance of urinary and fecal continence 1,3,8 , aid in increasing intra-abdominal pressure, in breathing and in stabilizing the body 1,6 . These muscles also allow sexual intercourse and childbirth; their involuntary contractions are the main characteristics of orgasm 6,7,9 and, when these muscles are weak, they can cause vaginal hypoesthesia and anorgasmia 7 . Therefore, PFMs can interfere negatively in female sexual function 10,11 .…”
Section: Introductionmentioning
confidence: 99%